Antiviral activity against dengue virus of diverse classes of algal sulfated polysaccharides - Pujol, Carlos Alberto (2012)
Diverse classes of sulfated polysaccharides obtained from the red seaweeds (Rhodophyta) Grateloupia indica, Scinaia hatei and Gracilaria corticata, the brown seaweeds (Phaeophyta) Stoechospermum marginatum and Cystoseira indica and the green seaweed (Chlorophyta) Caulerpa racemosa were assayed for antiviral activity against the four serotypes of dengue virus (DENV). DENV-2 was the most susceptible serotype to all polysulfates, with inhibitory concentration 50% values in the range 0.12-20. μg/mL. The antiviral potency of the sulfated polysaccharides depended on the sulfate content, the position of sulfate group, the sugar composition, and the molar mass. Independently of the sugar composition, the antiviral effect was mainly exerted during DENV-2 adsorption and internalization.